2023
DOI: 10.1002/anie.202218738
|View full text |Cite
|
Sign up to set email alerts
|

Direct Detection of FeVI Water Oxidation Intermediates in an Aqueous Solution

Abstract: In situ detection of highly‐oxidized metal intermediates is the key to identifying the active center of an oxygen evolution reaction (OER) catalyst, but it remains challenging for NiFe‐based catalysts in an aqueous solution under working conditions. Here, by utilizing the dynamic stability of the FeVIO42− intermediates in a self‐healing water oxidation cycle of NiFe‐based catalyst, the highly‐oxidized FeVI intermediates leached into the electrolyte are directly detected by simple spectroelectrochemistry. Our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…It has been proved that the self-healing of Fe active centers in the NiCoFe-B i catalyst is crucial to achieving stable freshwater oxidation under highly alkaline conditions. 29,37 Here, we believe that the activation of the selfhealing mechanism is also vital to the activity and stability of seawater oxidation under highly alkaline conditions. To prove this, we conducted a series of electrochemical tests concerning the effect of Fe(II) ions added to the alkaline artificial seawater.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proved that the self-healing of Fe active centers in the NiCoFe-B i catalyst is crucial to achieving stable freshwater oxidation under highly alkaline conditions. 29,37 Here, we believe that the activation of the selfhealing mechanism is also vital to the activity and stability of seawater oxidation under highly alkaline conditions. To prove this, we conducted a series of electrochemical tests concerning the effect of Fe(II) ions added to the alkaline artificial seawater.…”
Section: Resultsmentioning
confidence: 99%
“…S15, ESI†), the OER activity declined significantly compared with the NiCoFe-B i , because Co not only facilitates Fe redeposition but also promotes the formation of highly-oxidized Fe( vi ) intermediate species. 37 Furthermore, the self-healing effect was only found for Fe( ii ) ions added to the alkaline seawater, but not for the Ni( ii ) or Co( ii ) ions (Fig. S16, ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…The gradient Mg:Ta 3 N 5 photoanode was fabricated following our previously reported method. 19 Aer modifying the surface of the Mg:Ta 3 N 5 photoanode with a highly efficient borateintercalated nickel cobalt iron oxyhydroxide (NiCoFe-B i ) OER co-catalyst, 20,21 the PEC performance of the photoanode for the OER half reaction was tested in a standard three-electrode conguration. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[ 23 ] Nevertheless, some studies found that the high activity of Ni of unary Ni‐based catalysts may be an illusion—it is the Fe impurities in the electrolyte that dramatically improve the performance. [ 24 ] Moreover, shorter FeO bonds [ 25–26 ] and Fe 4+[ 27–29 ] were observed during the OER in binary FeNi‐based OER catalysts, providing strong evidence for Fe being the active site.…”
Section: Introductionmentioning
confidence: 99%